Changes in global quality of life after treatment with immune checkpoint inhibitors in patients receiving different treatment regimens for advanced stage lung cancer in the Netherlands: a 2015–2021 cohort study - Manuela Quaresma; Bernard Rachet; Geertruida H De Bock; Clémence Leyrat; Willemijn J Maas; Erick Suazo-Zepeda; Ananya Malhotra; Petra C Vinke; Jeroen T J.N Hiltermann (BMJ Open)
Background The introduction of immune checkpoint inhibitors (ICIs) has modified treatment modalities for patients with lung cancer, offering new alternatives for treatment. Despite improved survival benefits, ICIs may cause side effects impacting patients’ quality of life (QoL). We aim to study the changes in global QoL (gQoL) of patients with advanced-stage lung cancer up to 18 months after treatment with ICIs between 2015 and 2021.Methods and analysis A longitudinal cohort study was conducted using the Oncological Life Study: Living well as a cancer survivor data-biobank from the University Medical Center Groningen. Participants completed the European Organisation for Research and Treatment of Cancer QoL 30-item questionnaire, at the beginning of their ICI treatment (baseline) and then at 6, 12 and 18 months. Using joint modelling, changes in predicted mean gQoL were studied by treatment regimens from baseline to 18 months, while accounting for the competing risk of death and adjusting for prespecified covariates.Results Of the 418 participants with median age of 66 years, 39% were women. Patients receiving first-line immuno-monotherapy with palliative intent had a small improvement in their gQoL within 6 months and no clinically significant change thereafter. Patients receiving first-line immune-chemotherapy with palliative intent had a small improvement in their gQoL within 12 months and no clinically significant change thereafter. Patients with second/further line immunotherapy with palliative intent or first-line chemoradiotherapy followed by durvalumab with curative intent had no clinically significant change in their gQoL over 18 months.Conclusion The changes in gQoL over time among patients with advanced-stage lung cancer may vary by treatment regimens based on drug intensity, line and intent of treatment, which will help clinicians and patients understand the potential dynamic of treatments on QoL. It may further influence treatment decisions and patient management strategies, reflecting the practical implications of different treatment regimens.